2022
DOI: 10.3390/cancers14041016
|View full text |Cite
|
Sign up to set email alerts
|

Role of Radiology in the Preoperative Detection of Arterial Calcification and Celiac Trunk Stenosis and Its Association with Anastomotic Leakage Post Esophagectomy, an Up-to-Date Review of the Literature

Abstract: Surgical resection of the esophagus remains a critical component of the multimodal treatment of esophageal cancer. Anastomotic leakage (AL) is the most significant complication following esophagectomy, in terms of clinical implications. Identifying risk factors for AL is important for modifying patient management and improving surgical outcomes. This review aims to examine the role of radiological risk factors for AL after esophagectomy, and in particular, arterial calcification and celiac trunk stenosis. Elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Furthermore, not all the patients probably will benefit from GIC before esophagectomy, but it is likely that some high-risk individuals could be good candidates. 63,64 More specifically, patients with poor preoperative vascular status, major calcification of the thoracic aorta, and stenosis of the celiac axis could hypothetically benefit from GIC before esophagectomy. 65 To our knowledge, this is the first network analysis on this topic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, not all the patients probably will benefit from GIC before esophagectomy, but it is likely that some high-risk individuals could be good candidates. 63,64 More specifically, patients with poor preoperative vascular status, major calcification of the thoracic aorta, and stenosis of the celiac axis could hypothetically benefit from GIC before esophagectomy. 65 To our knowledge, this is the first network analysis on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…In the present meta-analysis, none of the included studies reported specific data on operating surgeons’ proficiency; therefore, results may be biased and should be interpreted prudently. Furthermore, not all the patients probably will benefit from GIC before esophagectomy, but it is likely that some high-risk individuals could be good candidates 63,64 . More specifically, patients with poor preoperative vascular status, major calcification of the thoracic aorta, and stenosis of the celiac axis could hypothetically benefit from GIC before esophagectomy 65…”
Section: Discussionmentioning
confidence: 99%
“…However, this procedure is technically challenging and requires expertise in ultrasound imaging, visceral arterial hemodynamics, and duplex scan interpretation. On the other hand, CTA with 2D and 3D imaging can provide excellent reconstructions of the visceral arteries and is recommended as the initial imaging study in many studies [4,[27][28][29][30][31][32][33][34][35][36][37]. Furthermore, centerline analysis may be helpful in increasing the accuracy of the measurement of the stenosis and is especially appropriate for preoperative planning of endovascular treatment.…”
Section: Discussionmentioning
confidence: 99%